Statistical analysis of congenital anomlies in children in Lithuania - Radavičius, Marijus; Sušinskas, Jurgis; Utkus, Algirdas (Lietuvos matematikos rinkinys, 2001)
Trends, prevalence and some influential (risk) factors of congenital anomlies in children in Lithuania are investigated using logistic regression model.